ANALISIS SIKAP DAN PERILAKU MASYARAKAT TERHADAP PELAKSANAAN PROGRAM BANK SAMPAH (Studi Kasus Masyarakat Kelurahan Bahagia Bekasi Utara) - Kurniawati Mulyanti; A Fachrurozi (Optimal: Jurnal Ekonomi dan Kewirausahaan, 2016)
This study aims to determine how the attitudes and behavior of people in the Village of Bahagia, North Bekasi against Bank Sampah Program Implementation in village Bahagia. This study used quantitative descriptive research method in which researchers will explain or describe public attitudes Bahagia Village North Bekasi, on the implementation of Bank Sampah Program in the Environment village Bahagia.This study used primary data by collecting data through questionnaires to 67 respondents that people in the Bahagia village, North Bekasi who follow the customer in the Sampah Bank in RW 45 Village Bahagia. Data were processed using descriptive statistical analysis to determine the public's attitude Bahagia Village North Bekasi on the implementation of the Bank Sampah Program. From the results of the average score of respondents about public attitudes confidence in the attributes of 0.74 which means that the public attitude of society Bahagia village good attitude towards the implementation of the existing Bank Sampah program such village. While based on the scores for variables Behavior of 0.66 (positive) means showing the behavior of people in the Bahagia village good or positive to the presence of Bank Sampah in its environment. From the discussion, it can be known factors - factors that need to be fixed for the implementation of the next program to the Bank Sampah. So need a better effort for the implementation of the Bank Sampah program.